2020
DOI: 10.1007/s40670-020-01165-y
|View full text |Cite
|
Sign up to set email alerts
|

Online-Learning due to COVID-19 Improved Mental Health Among Medical Students

Abstract: In reference to the announcement of the pandemic of the new coronavirus 2019-(nCoV), all educational institutions in the Republic of Kazakhstan have switched to online learning (OL). The purpose of this study was to investigate the mental state of the medical students switching to OL in comparison with the mental state of the students who had traditional learning (TL). A repeated questionnaire-based cross-sectional study was conducted among medical students ranging from 1st year to 5th year at Astana Medical U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
167
4
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(190 citation statements)
references
References 45 publications
10
167
4
9
Order By: Relevance
“…49 Interestingly, a cross-sectional study showed that medical students' burnout syndrome, depression, anxiety and somatic symptoms rates decreased during online learning. 62 On the contrary, sleep quality of medical students appears to have deteriorated during the pandemic, with insomnia, difficulties falling asleep and frequent awakening during the night being commonly reported. Decreased appetite was also reported.…”
Section: Mental Healthmentioning
confidence: 99%
“…49 Interestingly, a cross-sectional study showed that medical students' burnout syndrome, depression, anxiety and somatic symptoms rates decreased during online learning. 62 On the contrary, sleep quality of medical students appears to have deteriorated during the pandemic, with insomnia, difficulties falling asleep and frequent awakening during the night being commonly reported. Decreased appetite was also reported.…”
Section: Mental Healthmentioning
confidence: 99%
“…There is now a large body of published, peer‐reviewed research papers assessing the impacts of the pandemic on university students, the majority of these are surveys investigating topics such as student adaptations to online learning, 9–16 Covid‐19 impacts on mental health, 4,5,17–26 or less frequently, both of these factors in parallel 27–30 . Other studies that have taken a broader approach to understand how the pandemic has altered academic, societal, health, lifestyle and behavioural elements of the student experience 31–35 .…”
Section: Introductionmentioning
confidence: 99%
“…There is now a large body of published, peer-reviewed research papers assessing the impacts of the pandemic on university students, the majority of these are surveys investigating topics such as student adaptations to online learning, [9][10][11][12][13][14][15][16] Covid-19 impacts on mental health, 4,5,[17][18][19][20][21][22][23][24][25][26] or less frequently, both of these factors in parallel. [27][28][29][30] Other studies that have taken a broader approach to understand how the pandemic has altered academic, societal, health, lifestyle and behavioural elements of the student experience. [31][32][33][34][35] In this commentary we seek to focus more on the medical impacts, and particularly the enormous practical public health challenges posed by the Covid-19 pandemic for university students.…”
mentioning
confidence: 99%
“… 28 Another study found that e-learning improved medical students’ mental health and decreased their burnout levels. 29 Findings on medical student satisfaction with e-learning programmes and online teaching are currently mixed. In some places, medical students readily accepted the changes in the education format, 30 31 while others reported that students still preferred face-to-face teaching.…”
Section: Introductionmentioning
confidence: 99%